2023
DOI: 10.1021/acs.nanolett.2c04792
|View full text |Cite
|
Sign up to set email alerts
|

Giant and Tunable Excitonic Optical Anisotropy in Single-Crystal Halide Perovskites

Abstract: During the last years, giant optical anisotropy has demonstrated its paramount importance for light manipulation. In spite of recent advances in the field, the achievement of continuous tunability of optical anisotropy remains an outstanding challenge. Here, we present a solution to the problem through the chemical alteration of halogen atoms in single-crystal halide perovskites. As a result, we manage to continually modify the optical anisotropy by 0.14. We also discover that the halide perovskite can demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…When the energy falls from 2.330 to 2.270 eV, the n g of the V-cavity reduces from 7.4 to 4.3, and the n g of the U-cavity decreases from 10.3 to 7.7. When the resonant route is fixed, the n g at each energy is independent of the W , similar to the fact that Rabi splitting is relatively insensitive to cavity length in this cavity size range. ,, The difference of the n g between U-cavity and V-cavity can be affected by the crystal anisotropy and the effective mode volume. , Therefore, both the E – k ⊥ dispersion relation and the slow-light effect prove the existence of two folded F–P microcavity exciton polaritons.…”
Section: Resultsmentioning
confidence: 74%
“…When the energy falls from 2.330 to 2.270 eV, the n g of the V-cavity reduces from 7.4 to 4.3, and the n g of the U-cavity decreases from 10.3 to 7.7. When the resonant route is fixed, the n g at each energy is independent of the W , similar to the fact that Rabi splitting is relatively insensitive to cavity length in this cavity size range. ,, The difference of the n g between U-cavity and V-cavity can be affected by the crystal anisotropy and the effective mode volume. , Therefore, both the E – k ⊥ dispersion relation and the slow-light effect prove the existence of two folded F–P microcavity exciton polaritons.…”
Section: Resultsmentioning
confidence: 74%
“…In addition to this, we compared the resulting dielectric function of our CVD-grown sample with the first-principle calculations and dielectric function of molecular beam epitaxy (MBE)-grown Bi2Se3, reported by Fang and colleagues [40]. Interestingly, our recent publications [12,65] have shown that DFT dielectric function coincides with the optical response of monocrystals (an almost perfect match for n and a qualitative match with k), which in the case of layered materials are usually prepared using the exfoliation technique [66]. Hence, we can safely assume that DFT optical constants correspond with exfoliated Bi2Se3.…”
Section: Spectrocopic Ellipsometry Of Bi 2 Sementioning
confidence: 96%
“…The transparent regions of these materials are identified using symbols. f) Comparison of the absolute birefringence values of Sr 9/8 TiS 3 and a variety of anisotropic materials (from the literature [19,20,24,[28][29][30][31][32][33][34][35][36][37] ), showing that Sr 9/8 TiS 3 has by far the largest birefringence among reported anisotropic crystals. The symbols indicate regions of transparency.…”
Section: Introductionmentioning
confidence: 99%